Myoclonic epilepsy with ragged-red fibers: A case report - YU, XUE-FAN (Exp Ther Med, 2015)
Myoclonic epilepsy with ragged-red fibers is a maternally inherited disease that is characterized by myoclonic epilepsy, cerebellar ataxia and progressive muscular weakness. The present study reports the case of a 25-year-old male who presented with paroxysmal left upper limb tics and weakness for two years. Neurological examination revealed intact cranial nerves, decreased deep tendon reflexes and decreased sensation of touch, pain and vibration. The gait of the patient was broad and he was unable to walk in a straight line. Local cortical atrophy was also observed in the left temporal-occipital cortex on a magnetic resonance imaging scan. The muscle biopsy revealed ragged-red fibers. Therefore, the present study hypothesized that imaging observations and follow-up examinations are important in patients with myoclonic epilepsy.